OPTIMAL COMPOSITIONS FOR LOCAL CELLULAR CONCRETE RAW MATERIALS - Mamatov Xamidulla Abdullyevich; Sabirova Dilfuza Tillavaldievna (Journals Park Publishing, 2022)
This article is devoted to the issues of raw materials and the optimal composition of cellular concretes such as foam concrete and aerated concrete. In addition, information is provided on the strength, thermal conductivity, porosity, hardening conditions, bearing capacity, frost resistance, water absorption, fire resistance, environmental friendliness and durability of the material.
Keywords: improving the energy efficiency of buildings and structures, energy resources, thermal insulation, energy efficiency in the design of buildings